A Multi-dimensional Subcontractor Evaluation Framework for Nonconventional Housing Systems. (2017) - Basu, Riddha; Nanyam, V.P.S. Nihar; Sawhney, Anil
Abstract: For any building construction project, it is crucial at the outset to select an appropriate subcontractor to achieve the objectives in terms of affordability and quality. But selection of a competent subcontractor becomes even more important when it comes to housing-construction with non-conventional materials and technologies, as their implementation requires unique skills and proficiencies. In the first phase of this research, the subcontractor selection attributes were identified. Apart from literature review, divergent stakeholders of Indian real-estate value-chain were also surveyed for identification of subcontractor selection attributes. While some of the identified attributes are generic, others are specific towards selection of subcontractors for building construction with new materials and technologies. However, the identified attributes can be broadly classified into five categories: " technical experience", "financial competency", "resource adequacy", "job quality and safety" and " local and other factors" . In the next phase of the research, a multidimensional framework was developed using Analytical Hierarchy Process (AHP) for evaluation of subcontractors based on the identified attributes. The developed framework can also be used as a decision making protocol for selection of subcontractors for non-conventional building construction. The developed framework was validated by implementing it for subcontractor selection in a residential project site where emerging construction technologies were being implemented.